Isolation of xylanolytic bacteria from landfill soil and production of enzyme from the isolate - Nur Idayu, Ab Wahab (2017)
Currently, all developing Asian countries facing problem related with the disposal of municipal solid waste due to the rapid economic transition and populations. Bacteria was well known for the ability to secrete the enzyme that can be used in degrading of municipal solid waste (MSW). The objectives of this study were to isolate the potential microorganism from landfill soil and the production of the xylanase from the isolate. Xylanolytic microorganisms were isolated from landfill soil while the production of xylanase was carried out in submerged fermentation. The fermentation process was performed by using xylan as substrate of carbon source under specific conditions of 37°C, 150 rpm and 72 hr of fermentation period. The number of microorganisms found in the landfill soil were 21 with different species of microorganism consisted of 15 number of gram negative and 6 number of gram positive bacteria. Among the 21 isolates, 7 isolates were xylanolytic microorganisms that able to produce xylanase. The best xylanolytic bacteria was namely C3 gave the highest xylanase activity (6.81 U/mL) during 24 hr of fermentation. As a conclusion, the xylanolytic bacteria has an ability in producing the xylanase that can be used for the degradation process of MSW.